Enhancing Customer Understanding Through Instructional Video: The Development of Livin’ Merchant Guide at Bank Mandiri Area Purwokerto - Ardina Lulu Khirsasi; Lutfiana Lutfiana (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2026)
The author developed an informational video of using Livin’ Merchant during the internship at Bank Mandiri Area Purwokerto in the Transaction Banking Retail division as their focus on Livin’ Merchant with the aim as a guidance to explain about the features of Livin’ Merchant for customers. Additionally, the project was produced to find out any obstacles encountered in promoting and assisting customers with Livin’ Merchant. There are three methods were used by the author, namely observation, interview, and documentation. The interview conducted to enhanced the reliability of the information gathered. The documentation was conducted to provide data documentation to gain a clearer understanding within company. By gained data through the guide book of Livin’ Merchant, the author developing the informational video that reflects the features and benefits of Livin’ Merchant with combination of visuals and narration. Production including video recording, voice recording, and voice recording. The production process of developing an informational video including were pre-production that including generating idea, scriptwriting, and storyboarding. Post-production including final stage to finalized the edit to make sure everything aligned with the storyboard and script. Obstacle that author faced during developing the informational video were the lacked of generating idea and the platform for uploading the author's product was not available. The author overcomes the obstacles with gathering feedbacks from mentors and supervisors to gained ideas about Livin’ Merchant.